OFR-24-80 Determination Of Breathing Zone Concentrations Of Contaminants From Emissions From Diesel Powered Vehicles In Underground Mines - Walter D. Holland (The National Institute for Occupational Safety and Health (NIOSH), 1978)
This study was undertaken to determine miners' breathing zone concentrations of diesel exhaust components, to investigate any relationships between these concentrations and vehicle type, the presence of emission controls, vehicle usage, and ventilation conditions, and to make recommendations for monitoring and ventilation requirements. Twenty-four mines including two con l mines were surveyed. Sampling was done for CON, NON, SOx, PNA, aldehydes, and particulates. hi most mines, concentrations of at least one contaminant exceeded one half the standard or TLV. The concentrations of gases arc probably sufficiently reduced by a minimum air velocity of 50 fpm. A sufficient reduction of particulate concentrations may require as high as 400 fpm air velocity. Vehicle age, type, or usage appear to have little or no effect on contaminant concentrations. PNA levels were below detection limits in all but a very few samples. Minimum requirements for routine monitoring should include formaldehyde, COx, NO2. It is further recommended that better definition of the minimum ventilation requirement be obtained.